Effects of combined protein and exercise interventions on bone health in middle-aged and older adults — A systematic literature review and meta-analysis of randomized controlled trials - Wolf, Julia; Schöne, Daniel; Kohl, Matthias; Kemmler, Wolfgang; Kiesswetter, Eva (Osteoporosis international, 2025)
Purpose: Osteoporosis has become a global public health concern making prevention and treatment essential to reduce severe consequences for individuals and health systems. This systematic review with meta-analysis aimed to determine the effects of combined protein and exercise interventions compared to (a) exercise alone and (b) protein alone on bone mineral content (BMC) or density (BMD) in middle-aged and older adults. Methods: We systematically searched Medline, CINAHL, CENTRAL, Web of Science, and SPORTDiscus until 24th January 2023. Pairwise random-effects meta-analyses were performed to calculate weighted mean differences (WMD) with 95% confidence intervals (95% CI). We evaluated risk of bias (Cochrane RoB2) and certainty of evidence (CoE; GRADE). If pooling was not possible, the results were summarized descriptively. Results: For the comparison of combined protein supplementation and exercise vs. exercise alone, no meta-analysis for BMD (2 RCTs) was possible. For BMC, little to no intervention effect was found (WMD 0.03 kg; 95% CI − 0.00 to 0.05; 4 RCTs; IG = 97/CG = 98; I2 = 58.4%). In a sensitivity analysis, restricted to combined milk-protein supplementation and exercise, the result remained similar (0.01 kg; 95% CI − 0.01 to 0.03; 4 RCTs; IG = 71/CG = 71; I2 = 0.0%; low CoE). For the comparison of combined protein and exercise interventions vs. protein alone, no RCT on BMC was identified; the results on total or regional BMD (2 RCTs) were inconclusive. Conclusion: Based on our findings, no robust conclusions can be drawn on whether combining protein and exercise interventions is more beneficial for bone health than one component alone. Sufficiently powered studies with longer duration are required to clarify these questions (CRD42022334026).
CRIS-Team Scopus Importer:2025-02-21
Keywords: Bone health; Protein and exercise interventions; Randomized controlled trials